2014
DOI: 10.3791/51581
|View full text |Cite
|
Sign up to set email alerts
|

Method for Obtaining Primary Ovarian Cancer Cells From Solid Specimens

Abstract: Reliable tools for investigating ovarian cancer initiation and progression are urgently needed. While the use of ovarian cancer cell lines remains a valuable tool for understanding ovarian cancer, their use has many limitations. These include the lack of heterogeneity and the plethora of genetic alterations associated with extended in vitro passaging. Here we describe a method that allows for rapid establishment of primary ovarian cancer cells form solid clinical specimens collected at the time of surgery. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Our panel was optimized for single-cell suspensions obtained from primary tumor samples, and the six dissociation methods were selected to cover the spectrum of regular dissociation protocols applied to ovarian tumors [13,46]. In our study, we found that the method of tissue dissociation affected the marker expression of a few subgroups within the three major cell subsets.…”
Section: Discussionmentioning
confidence: 90%
“…Our panel was optimized for single-cell suspensions obtained from primary tumor samples, and the six dissociation methods were selected to cover the spectrum of regular dissociation protocols applied to ovarian tumors [13,46]. In our study, we found that the method of tissue dissociation affected the marker expression of a few subgroups within the three major cell subsets.…”
Section: Discussionmentioning
confidence: 90%
“…Ovarian Surface Epithelial (OSE) cells and primary ovarian cancer cells were isolated from ovarian specimens excised from patients undergoing oophorectomy for benign conditions and cultured as we have previously described (17, 19, 20). …”
Section: Methodsmentioning
confidence: 99%
“…Primary ovarian cancer cells were isolated from solid specimens using the modified method described by Pribyl et al . 77 . The tissue pieces were digested with 150 U/mL collagenase (Sigma-Aldrich, St. Louis, MO, USA) for 30 min at 37 °C and then transferred onto a nylon cell strainer (100 µm; VWR International, Radnor, PA) to separate EOC cells.…”
Section: Methodsmentioning
confidence: 99%